Disruption of Labor Regime and Precarious Work as Hidden Features of Flexible Capitalism - Poplavskaya, Anita (Journal of Economic Sociology, 2017)
Benjamin Snyder’s book, “The Disrupted Workplace: Time and the Moral Order of Flexible Capitalism,” is devoted to the subjective perception of time spent at work by the employees who work under the system of flexible capitalism. The author describes two types of time perception: quantitative, expressed in the desire to adhere to clear schedules and plans, and qualitative, marked by the ability to respond quickly to external changes and be constantly ready to act. The first type remains to be the reference for the classical worker and the most convenient one, but it is becoming rare in the labor market. The second type is modern and more universal among employees now, but it has significant shortcomings. The interviews conducted with three groups of respondents (financial professionals, truck drivers, and unemployed job seekers), showed which dilemmas, contradictions, and disorders flexible capitalism has. At the outset, the system seems to provide the employee with opportunities to work freely, be entrepreneurial, change his life for the better, and have flexible working hours. Then it becomes clear that the workers lose themselves in unstructured labor regimes, chaotic tasks, insecure working positions, and the absence of predictable future career paths, which deprives them of the opportunities to develop safely in the sphere of work and to plan their own futures. The situation, according to the author, is critical. “Games with work” forcing the workers to sacrifice their health, personal lives, and sometimes even rights to have a job and get a decent salary, stimulates them to be in a constant race to fulfil current tasks (in the case of financial professionals and drivers) or to search for a job (in the case of the unemployed). In such conditions, people have no opportunity to revitalize physically, morally, and psychologically. It becomes harder for them to critically estimate the modern system of flexible capitalism and their positions within this system. Justifying desynchronized life rhythm and constant change by the avoidance of monotony, boredom, and the routine of classic labor regimes at the micro level, society comes across new forms of inequality (highly skilled specialists are exposed to unemployment on par with low-skilled workers) and problems with job security (work becomes irregular and unpredictable for the majority of the population) at the macro level.